Jagiellonianism in Poland and Ukraine as a factor of university education and a cultural and historical phenomenon - Hysa, Oksana A.; Stepaniuk, Ihor V.; Vaniuha, Liudmyla S.; Zhorniak, Bogdana Ye; Rehulich, Iryna V. (Linguistics and Culture Review, 2021)
The relevance of the research topic consists in the necessity of a comprehensive study of the educational and scientific activities of the departments of musicology of Krakow and Lviv universities during the first half of the twentieth century in the context of coverage of the interaction experience between Ukrainian and foreign higher education institutions so to determine in such way the features and values of the Ukrainian music science in the European scientific and educational space. The purpose of the research is to discover and to analyze the creative activity of the departments of musicology at the Krakow and Lviv Universities in the context of Jagellonism through the consideration of the principles of European musical academic education since the establishment of these institutions in 1911-1912 and till the beginning of the XXI century. The scientific novelty of the research consists in finding out the leading role of Z. Jachimecky and A. Chybi?ski in the formation and development of national musicological schools in Poland and Ukraine as inheritors of the cultural genetic code of Jagiellonism. That cultural genetic code consisted of special attention to the inter-Slavic relations within the Western-Eastern cultural heritage.